Analisis Kadar b-Karoten Buah Pisang Raja (Musa Paradisiacal L) dan Pisang Kepok (Musa Paradisiaca Forma Typica) dengan Metode Spektrofotometri UV-Vis - Zarnila, Zarnila; Napitupulu, Mery; Jura, Minarni Rama (Jurnal Akademika Kimia, 2018)
Banana fruit is a fruit that contains many nutrients. One of that is b-carotene, b-carotene is a provitamin that plays an important role in the formation of vitamin A. This study aimed to determine the levels of Î²-carotene in raja and kepok bananas. This research used a qualitative and quantitative method, which is the qualitative method using TLC while the quantitative method using UV-Vis spectrophotometry. The TLC results obtained that Rf b-carotene comparison was 0.97 cm, Rf of banana raja extract was 0.96 cm and banana kepok extract was 0.97 cm. Based on the UV-Vis spectrophotometry result, b-carotene content of raja banana fruit was 0.222 mg/100 grams while the kepok banana fruit was 0.261 mg/100 grams, therefore the highest level was banana kepok.